Noise-Disturbance Relation and the Galois Connection of Quantum Measurements - Carmeli C; Heinosaari T; Miyadera T; Toigo A (SPRINGER, 2022)
The relation between noise and disturbance is investigated within the general framework of Galois connections. Within this framework, we introduce the notion of leak of information, mathematically defined as one of the two closure maps arising from the observable-channel compatibility relation. We provide a physical interpretation for it, and we give a comparison with the analogous closure maps associated with joint measurability and simulability for quantum observables.